Inverse Design of Diffractive Relativistic Meta‐Sails via Multi‐Objective Optimization. Issue 6 (25th April 2021) - Salary, Mohammad Mahdi; Mosallaei, Hossein
Abstract: Photonic propulsion of light sails using the radiation pressure of an intense laser beam is a promising route to achieve relativistic velocities for deep space exploration. A successful photonic design of such relativistic sails requires efficient acceleration and maintaining stability of the beam‐riding across a Doppler‐broadened propulsion band due to considerable red‐shift of the wavelength in the frame of the moving sail. While efficient acceleration of the sail requires maximizing the optical force along the beam propagation direction, the stability degree of the sail depends on the magnitude of lateral forces in the transverse plane of the beam. This establishes a trade‐off between these two requirements which calls for their synergistic engineering. In this work, an evolutionary multi‐objective optimization technique for the inverse design of diffractive relativistic meta‐sails with a genetic pixelated geometry is adopted. The goal is to identify a set of Pareto optimal solutions which provides the designer with an intuitive understanding of the ultimate trade‐off between acceleration and stability degree of the sail in a vast design space, and allows for a well‐informed decision on the best design given the requirements for the acceleration time and distance as well as the tolerance with respect to mispointings and misalignments. Abstract : In this work, an evolutionary multi‐objective optimization technique is adopted for the inverse design of diffractive relativistic meta‐sails with a genetic pixelated geometry. The goal is to identify a set of Pareto optimal solutions which provides the designer with an intuitive understanding of the ultimate trade‐off between acceleration and stability degree of the sail in a vast design space.